2015
DOI: 10.1002/cyto.a.22681
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of flow‐cytometric estimation of nuclear genome size in orchids, a plant group with both whole‐genome and progressively partial endoreplication

Abstract: Nuclear genome size is an inherited quantitative trait of eukaryotic organisms with both practical and biological consequences. A detailed analysis of major families is a promising approach to fully understand the biological meaning of the extensive variation in genome size in plants. Although Orchidaceae accounts for $10% of the angiosperm diversity, the knowledge of patterns and dynamics of their genome size is limited, in part due to difficulties in flow cytometric analyses. Cells in various somatic tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 36 publications
2
77
0
Order By: Relevance
“…Previous measurements showed the occurrence of endoreplication in the samples – as commonly cited for Orchidaceae (Trávníček et al . ). It requires a reference standard with GS, which is not so similar to studied species, in order to avoid overlapping peaks (see Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Previous measurements showed the occurrence of endoreplication in the samples – as commonly cited for Orchidaceae (Trávníček et al . ). It requires a reference standard with GS, which is not so similar to studied species, in order to avoid overlapping peaks (see Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Overall, the potential of estimating flow cytometry DNA content in plant science has not been fully explored. Recent studies based on this method have revealed new phenomena in plant science (70)(71)(72) or new applications of the method (73). The present study highlights the use of FCM methodology, a powerful and precise tool for DNA content estimation, in plant reproduction biology.…”
Section: Application Of Fcss In Reproductive Biologymentioning
confidence: 70%
“…Recent studies based on this method have revealed new phenomena in plant science (70)(71)(72) or new applications of the method (73). Overall, the potential of estimating flow cytometry DNA content in plant science has not been fully explored.…”
Section: Application Of Fcss In Reproductive Biologymentioning
confidence: 99%
“…In recent times, flow cytometry has become the preferred method to estimate nuclear DNA contents in plants, not only because it is fast, reproducible and enables analysis of thousands of particles, but also because it only requires small amounts of tissue (Doležel et al, 2007). Nonetheless, this is not always straightforward, and several taxonomic groups pose challenges due to either the presence of cytosolic compounds or unbalanced numbers of nuclei in G1-phase of mitosis, which may lead to misinterpretation of the resulting flow histograms (Trávníček et al, 2015). Orchids are sometimes challenging due to frequent rounds of endoreplication (including partial endoreplication), which might be tissue-specific, hence efforts have focused in searching for alternatives in order to overcome this problem (e.g.…”
Section: The Use Of Alternative Tissues To Estimate Gs and Infer Ploimentioning
confidence: 99%
“…Orchids are sometimes challenging due to frequent rounds of endoreplication (including partial endoreplication), which might be tissue-specific, hence efforts have focused in searching for alternatives in order to overcome this problem (e.g. Pellicer and Leitch, 2014;Trávníček et al, 2015). In our study, although Ophrys does not seem to represent a major challenge in this respect, we investigated the use of pollinaria for estimating nuclear DNA contents and allocating DNA-ploidies instead of leaves.…”
Section: The Use Of Alternative Tissues To Estimate Gs and Infer Ploimentioning
confidence: 99%